2019
DOI: 10.1088/1748-9326/ab0921
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of a coniferous woodland persistence under drought and heat

Abstract: Predictions of warmer droughts causing increasing forest mortality are becoming abundant, yet few studies have investigated the mechanisms of forest persistence. To examine the resistance of forests to warmer droughts, we used a five-year precipitation reduction (∼45% removal), heat (+4°C above ambient) and combined drought and heat experiment in an isolated stand of mature Pinus edulis-Juniperus monosperma. Despite severe experimental drought and heating, no trees died, and we observed only minor evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 66 publications
(84 reference statements)
1
66
0
1
Order By: Relevance
“…This is important given that climate models for the southwestern USA consistently agree that temperatures will increase in the coming century (Cook et al, 2015) and that warmer conditions during drought have been shown to hasten mortality in stands composed of pine ( Pinus spp. ; Breshears et al, 2018; McDowell et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important given that climate models for the southwestern USA consistently agree that temperatures will increase in the coming century (Cook et al, 2015) and that warmer conditions during drought have been shown to hasten mortality in stands composed of pine ( Pinus spp. ; Breshears et al, 2018; McDowell et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This benefit is relevant for forests across a broad range of aridity conditions (Gleason et al, 2017), and particularly for the ~28% of global forests (25.2 million km 2 ) that occur in in dry sub‐humid, semi‐arid or drier conditions (Figure 6). Density reduction in dry forest ecosystems not only sustains growth and boosts resilience to drought, but also produces many co‐benefits that increase overall ecosystem health, including resistance and resilience to wildfire (Ziegler et al, 2017), decreased susceptibility to insect outbreak (Kolb et al, 2016), increased regeneration (Kolb et al, 2020) and decreased risk of mortality during drought events (Breshears et al, 2018), benefits that are likely to become even more important as temperatures rise and hydrologic regimes shift in coming decades (Bradford & Bell, 2017; McDowell et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Events of extensive tree dieback and mortality related to drought have been detected across the world and described in several papers (Gitlin et al, 2006;Allen et al, 2010Allen et al, , 2015Anderegg et al, 2013Anderegg et al, , 2015Choat et al, 2018). Increasing drought conditions, together with rising temperatures, weaken trees making them prone to insect and pathogen attacks that in some cases are the ultimate cause of tree death (Dobbertin et al, 2007;Wermelinger et al, 2007;Anderegg et al, 2015;McDowell et al, 2019). In Europe, a large body of literature deals with the dieback of Scots pine (Pinus sylvestris L.) at the southernmost portion of its range (see Bussotti et al, 2014Bussotti et al, , 2015 for review), especially in Valais, Switzerland (Rigling et al, 2013) and Spain (Vilà-Cabrera et al, 2011).…”
mentioning
confidence: 99%
“…If mass/stiffness indicators are not available to guide analyzing τ , we suggest monitoring τ can still be used as a relative indicator of hydraulic status in different trees and across larger spatial scales, but should be monitored in conjunction with other metrics in both wet and dry conditions as indicated by soil moisture or additional tree‐derived responses, such as leaf and/or stem water potential and sap flow. Lastly, we recommend comparing τ signals in trees experiencing water stress with τ signals on the same days in trees that may be buffered from developing water stress, such as forested areas with different soil types or with differential access to deeper reservoirs of soil water (McDowell et al, ).…”
Section: Discussionmentioning
confidence: 99%